ANALISIS SWOT SEBAGAI DASAR PENYUSUNAN STRATEGI PENGEMBANGAN PEMBELAJARAN PENDIDIKAN JASMANI DI SDLB NEGERI WIRADESA - Eka Shanti Aulia; Irshofa Hany; Aisyah Rahmalia; Salma Fitriani Novanda; Rizqi Amalia; Andung Dwi Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Physical education instruction for students with special needs at SDLB Negeri Wiradesa continues to face a range of operational constraints, including limited adaptive teaching facilities, class sizes exceeding ideal capacity, and the absence of a development strategy grounded in the school’s actual conditions. This study aims to examine the condition of physical education learning in terms of its strengths, weaknesses, opportunities, and threats, and to formulate a corresponding development strategy through SWOT analysis. A descriptive qualitative approach was employed, with a physical education teacher selected through purposive sampling as the research subject, data were collected through semi-structured interviews, observation, and document review, then analyzed using a SWOT matrix. Findings reveal that teachers’ capacity to modify materials, methods, and media constitutes the primary strength, while limited adaptive facilities and oversized classes stand out as the most pressing weaknesses. Development opportunities emerge through the application of Problem Based Learning and Project Based Learning models alongside instructional video media, whereas communication barriers and inconsistent parental support at home represent threats requiring anticipation. Based on these findings, the recommended strategies include optimizing technology-based adaptive media, strengthening teacher–parent collaboration, and adopting flexible, learner-responsive teaching methods.